Decreasing microbial phosphorus limitation increases soil carbon release - Cui, Yongxing; Moorhead, Daryl L.; Wang, Xiangxiang; Xu, Mingzhe; Wang, Xia; Wei, Xiaomeng; Zhu, Zhenke; Ge, Tida; Peng, Shushi; Zhu, Biao; Zhang, Xingchang; Fang, Linchuan (Geoderma, 2022)
[Display omitted] •Soil P limitation constrains rather than promotes microbial C metabolism.•Removal of microbial P limitation by P addition increases CO2 release from soils by 19%–26%•Negative or positive relationship of microbial C and P limitations depend on soil C availability.•Alleviated microbial P limitation promotes soil C release via qCO2 and priming effect under C sufficiency.•Soil native C decomposition via priming effect dominates soil C release under C limitation. Phosphorus (P) limitation to microorganisms is increasingly recognized in soils, but how the limitation mediates the metabolic processes of microbes driving soil carbon (C) release remains unclear. Here, we performed a 60-day incubation experiment adding two 13C-labeled organic C sources (glucose and straw) at five inorganic P addition levels in loess with low available P from the Loess Plateau, China. The nutrient limitations of microbes were quantified by enzymatic vector analysis, associated with soil respiration, microbial metabolic quotient (qCO2), C use efficiency (CUE) and priming effect (PE) at both early (10 days) and late (60 days) stages of incubation. Results showed that reducing microbial P limitation increased CO2 release from soils by 19–26% and from labeled glucose and straw by 12% and 29%, respectively. This indicated that soil P limitation overall constrains rather than promotes microbial C metabolism. A negative relationship between relative C and P limitations at the first 10-day incubation further indicated that added P (decreased P-acquiring enzyme activities) stimulated microbial C metabolism (increased C-acquiring enzyme activities) under enough C source. Whereas a positive relationship at 60-day incubation suggested that high microbial heterotrophic respiration under high P addition alleviate their C limitation. Furthermore, both multiple regression and partial least squares path models indicated that an increase in CO2 release with P and C additions at early incubation was due to two processes, i.e., increasing available P promoted decomposition of native soil organic C due to PE as well as decay of added organic C by increasing qCO2 and decreasing CUE. At late incubation, however, P addition increasing decomposition of native soil C via PE is the dominated control on CO2 release under C limitation. We conclude that microbes are dominant by maintenance rather than growth metabolism in loess with low phosphorus availability, whereas the pathways of the metabolism driving C release depend on soil C availability. Our findings suggest that microbial P limitation has considerable positive effects on soil C sequestration in these ecosystems with low soil P availability.